Achilles Steel? Investigating Corrosive Capital in the Smederevo Železara Privatization - Ben, Reade (Journal of Regional Security, 2023)
The term “corrosive capital” has become a popular phrase in Serbia and across the Western Balkans used to describe opaque and scandalous foreign investments that are believed to enable state capture. Particularly in Serbia, existing approaches to corrosive capital have certainly identified which investments are problematic. However, there is still a lack of understanding about which key actors are culpable for corrosive investments and the practices that enable them. Responsibility is often binarily assigned, either to the Vučić regime or non-Western actors. This paper, however, uses qualitative and quantitative methods to more rigidly investigate the networked structures and practices that bring about corrosive capital. Through the development of an analytical framework and an investigation of the Smederevo Železera privatization, this paper argues that corrosive capital is a multi-level phenomenon enabled by interactions between various domestic and foreign actors used as a tool of state capture and personal enrichment. This paper also notes that informal practices and deal-making between these actors in a project’s early stages generate various spillovers that create an overall mosaic of corrosiveness.